Taxation if Capital is not Perfectly Mobile: Tax Competition versus Tax Exportation - Sylvester C.W. Eijffinger; Wolf Wagner (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
This paper analyzes the tax competition and tax exporting effect of financial integration. On the one hand, financial integration increases capital mobility and thus the incentive for countries to compete for capital. On the other hand, financial integration increases foreign ownership of firms and capital and allows for exportation of source taxes. Both effects have contrary implications for capital taxes. Allowing for imperfectly mobile capital, our analysis suggests that currently the tax exportation effect is dominating, which implies excessive capital taxation. From studying the benchmark of full financial integration we find that capital taxes are likely to increase from current levels. We further examine the tax exportation effect empirically and find that is significant as well as quantitatively important for the U.S.
Keywords: 330; Steuerwettbewerb; Finanzmarkt; Marktintegration; Kapitalmobilität; Optimale Besteuerung; Kapitalertragsteuer; Eigentümerstruktur; Theorie